2014
DOI: 10.1037/a0035074
|View full text |Cite
|
Sign up to set email alerts
|

Methodological concerns for meta-analyses of meditation: Comment on Sedlmeier et al. (2012).

Abstract: We commend Sedlmeier et al. (2012) for their significant undertaking of meta-analysis of all meditation types on all psychological variables, but additional analyses may modify some of their conclusions. Whereas they suggest from visual inspection of funnel diagrams that there may be publication bias of underreporting low-effect studies on the Transcendental Meditation (TM) technique, quantitative tests do not indicate the presence of bias for any type of meditation. We additionally found that there was no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…The results show that BKRY practitioners who adapt to the lifestyle changes experience a significant sense of progress in wellbeing. This is in line with other reports that show that meditation practitioners experience enhanced wellbeing on a number of measures (Manocha et al, 2012;Orme-Johnson & Dillbeck, 2014).…”
Section: Discussion Of Studysupporting
confidence: 93%
“…The results show that BKRY practitioners who adapt to the lifestyle changes experience a significant sense of progress in wellbeing. This is in line with other reports that show that meditation practitioners experience enhanced wellbeing on a number of measures (Manocha et al, 2012;Orme-Johnson & Dillbeck, 2014).…”
Section: Discussion Of Studysupporting
confidence: 93%
“…Due to the fact that yoga is a holistic way of life, the research method for yoga is always going to be weak. Along this line, a recent article on meditation research indicated that [yoga] research might be better served when it is driven by theory [34].…”
Section: B Develop a Theorymentioning
confidence: 96%
“…We calculated the mean weighted (by sample size) effect size of these three studies and found r ϭ .17, that is, an effect that is smaller than the average effect size we found in our original analysis for TM studies (r ϭ .27). Strictly speaking, Orme-Johnson and Dillbeck (2014) were right to contend that our coverage of TM studies was not complete. Indeed, meditation research has been performed by a very heterogeneous group of researchers and scattered across a huge range of journals.…”
Section: Was Our Search Complete?mentioning
confidence: 96%
“…Even the quite heterogeneous group of other meditation techniques sometimes scored highest, as for the variable we termed cognition. Orme-Johnson and Dillbeck (2014) have argued that these empirically found differences are inconsistent with the assumption of a uniform effect of meditation. They are very probably right.…”
Section: What Is the Appropriate Unit Of Analysis?mentioning
confidence: 99%
See 1 more Smart Citation